Resposta esperada à seleção correlacionada em uma população f6 de soja - REIS, EDESIO FIALHO DOS; Reis, Múcio Silva; Cruz, Cosme Damião; Sediyama, Tuneo; Sediyama, Carlos Sigueyuki (Revista Ceres, 2015)
-